Lake‐type controls on sedimentary infill and petroleum source rocks in the Palaeogene Fushan Depression, Beibuwan Basin, South China. (4th September 2019) - Jin, Siding; Wang, Hua; Cao, Haiyang; Gan, Huajun; Chen, Shanbin
Abstract : The lacustrine Beibuwan Basin contained large petroleum reserves in the northern continental shelf of the South China Sea. Due to the great sedimentologic complexity of the lacustrine basins, a significant financial risk associated with exploration needed to be reduced by specific techniques or significantly increasing knowledge of the lake system. Sedimentary infill, sequence stratigraphy, and organic geochemistry of the Fushan Depression in the Beibuwan Basin were studied, and enhanced our comprehension of the genetic relations between the sediment + water supply rates (climate change) and potential accommodation (tectonic subsidence and inherited topography) change. Here, we report two different lake‐type evolution cycles developed in two separated sags in the Fushan Depression, which are characterized by: (a) overfilled, (b) balanced‐fill, (c) overfilled, (d) balanced‐fill, and (e) overfilled in the Huangtong Sag, and (a) overfilled, (b) balanced‐fill, and (c) overfilled in the Bailian Sag and the centre Huachang Transfer Zone. Climate change is the dominant factor in the first three phases of the lake‐type evolution in both two sags, and transtensional tectonic setting is the controlling factor in the fourth and fifth phases of the lake‐type evolution in the Huangtong Sag. The same lake‐type with similar source rock and reservoir properties and observations indicate that these associations of source rock and reservoir play elements occur in a wide variety of tectonic settings. Moreover, the discovery of the cyclical process of the lake‐type evolution in the Fushan Depression can be a reference in the study of other similar lacustrine basins under an analogous tectonic and climate background.